2019
DOI: 10.1016/j.cbi.2019.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Diethylnitrosamine enhances hepatic tumorigenic pathways in mice fed with high fat diet (Hfd)

Abstract: Obesity has been implicated in the genesis of metabolic syndromes including insulin resistance and Type 2 Diabetes Mellitus (T2DM). Given the association between T2DM and the risk of hepatocellular carcinoma (HCC), our specific goal was to determine whether the liver of HFD-induced T2DM mice is more sensitive to the carcinogen diethylnitrosamine (DEN), due to a modification of the molecular pathways implicated in the early stages of HCC pathogenesis. C57BL/6 male mice (five-week-old) were divided into 4 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Upon activation, β-catenin translocates into the nucleus to competitively bind with TCF4 to form β-catenin/TCF4 complex. The complex then activates downstream transcription factors of TCF4, such as cycD and c-Myc, which ultimately leads to cell abnormalities, proliferation, and tumorigenesis [18,19]. Studies have shown that abnormal activation of the TCF4 target gene by Wnt signaling can promote malignant transformation of colorectal cancer [20], and downregulation of the Wnt/β-catenin signaling pathway can inhibit epithelial-mesenchymal transition in nonsmall cell lung cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, β-catenin translocates into the nucleus to competitively bind with TCF4 to form β-catenin/TCF4 complex. The complex then activates downstream transcription factors of TCF4, such as cycD and c-Myc, which ultimately leads to cell abnormalities, proliferation, and tumorigenesis [18,19]. Studies have shown that abnormal activation of the TCF4 target gene by Wnt signaling can promote malignant transformation of colorectal cancer [20], and downregulation of the Wnt/β-catenin signaling pathway can inhibit epithelial-mesenchymal transition in nonsmall cell lung cancer [21].…”
Section: Discussionmentioning
confidence: 99%
“…6,11 Based on the reduced lipid deposition in BHLivDKO mice, we examined whether the elimination of BMAL1 and HNF4α together was protective in the context of HCC. Using Hnf4a individual knockout mice (H4LivKO) as positive controls, we used DEN injection followed by HFD feeding to induce HCC, a combination of insults that has been shown to accelerate the growth of HCC 53,54 (Figure 2A). WT male and female mice were treated with DEN at day 15 and injected with tamoxifen for 5 days starting at 8 weeks of age.…”
Section: Hnf4α Suppresses Den-induced Hcc Formation and Il6 Activationmentioning
confidence: 99%
“…In MAFLD-HCC models, DEN is injected intraperitoneally into rodent models fed a HFD to induce HCC. Interestingly, it was reported that under a HFD background, HCC, inflammation, and fibrosis induced by DEN are exacerbated [ 292 , 293 ]. However, in these models, NASH, fibrosis is absent and is hence unable to capture the sequelae of MAFLD progression and consequently NASH-driven HCC [ 294 ].…”
Section: Mafld Preclinical Modelsmentioning
confidence: 99%